Comparison of anesthesia onset and duration between needle and needle-free methods in pediatric circumcision - Kumara, Y. Sigit; Aulawi, Khudazi; Pertiwi, Ariani Arista Putri (Jurnal Ners, 2025)
Introduction: Various anesthesia methods are utilized during circumcision, including needle anesthesia (NA) and needle-free anesthesia (NFA). However, research on differences in the total duration of anesthetic action between these methods remains limited. Therefore, this study aimed to evaluate the effectiveness of NA and NFA techniques in circumcision. Methods: This observational study employed a prospective cohort design and an independent t-test. A total of 56 participants were included, with 28 patients assigned to each technique. Data collection was conducted using an observation sheet. Consecutive sampling was applied, and the primary variables measured were the onset of anesthetic drug, duration of anesthetic effect, and total duration of anesthetic action. Results: The onset of anesthetic drug, measured as the time from administration to numbness, averaged 4.53 minutes and 3.14 minutes using the NA and NFA methods, respectively (p<0.001). The average duration of anesthetic effect, measured as the time from the onset of numbness to anesthesia dissipation, was 95.39 minutes and 79.00 minutes in the NA and NFA methods, respectively (p<0.001). Finally, the total duration of anesthetic action was 100.46 minutes and 82.54 minutes using the NA and NFA methods, respectively (p<0.001). Conclusions: The NFA method facilitates a faster onset, while the NA method provides a longer duration of anesthetic effect. These findings may assist clinicians in selecting anesthesia techniques based on procedural duration and patient comfort in pediatric circumcision. Further studies are suggested to explore other influencing factors.